HUBUNGAN PERSEPSI DAN DUKUNGAN KELUARGA DENGAN PEMILIHAN METODE KB MOP - Lelly Aprilia Vidayati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Male Contraception Methods Operative MOP is a minor operative contraception method in male is a very secure, simple and very effective, timeconsuming operation is very short and does not need general anesthesia. Of the 218 male is reproductive age, 11 person ( 5 % ) who use KB MOP. The purpose of this study was to analyze the relationship of perception and family support with the choice of family planning (KB) MOP methods at Polindes Tunas Bunda Meddelan Lenteng Sumenep . Independent variable is the perception, family support, while the dependent variable is the choice of KB MOP method. The usage of design study is a study analitic with cross sectional approach. The population of 218 male is reproductive age in Polindes Tunas Bunda Meddelan Lenteng Sumenep. The sample of 141 respondents, taken by purposive sampling. So the sample become 76 male respondents reproductive age which are fulfill KB MOP. The methods of data collection in the form of a questionare and analyzed using Chi Square. The results study showed that the choice of family planning MOP methods obtained which have a negative perception as many as 50 respondents ( 65.8 % ), while a positive perception as many as 26 respondents ( 34.2 % ). And family support that does not support as many as 50 respondents ( 65.8 % ), while supporting as many as 26 respondents ( 34.2 % ). On the result of the statistical test Chi Square using SPSS obtained there is a relationship of perception and support families with the choice of KB MOP Method in Polindes Tunas Bunda Meddelan Lenteng Sumenep. So it is obtained a value ρ value < α which means that ( 0.000 < 0.05 ), which means that H0 rejected and H1 accepted. Based on the above results are expected to midwives or health workers to provide counseling and information and about the benefits of family planning MOP regularly. In order for male of reproductive age want to choose and have a positive perception and family can support to KP MOP.